Microstructural and numerical variation of friction spot welded AA7075 couples - Sarsilmaz, Furkan; Celik, Buesra Gurocak (Walter de Gruyter Gmbh, 2023)
Friction stir spot welding (FSSW), which is one of the joining methods, is an interesting solid state joining process. In this experimental study, the joining of AA7075, which is the one of the Al-based alloys, with the FSSW method was conducted. Firstly, the microstructural inspections were performed by helping an optical microscope. Second, a numerical simulation study was performed using SolidWorks and ANSYS software. Therefore, these data were evaluated with modeling for understanding the events in zone of FSSW center. Thus, it could be contributed to understand the complex thermo-mechanical joining process period. The present simulation primarily aims to explain the effect of a set of process such as parameters and tool geometry on the workpiece couples. Johnson-Cook damage criteria model was selected to obtain the stress distribution on the workpiece couples consisting of AA7075. The model also showed that temperature and stress did not exhibit much appreciable change on flow with the change of the tip profile. As a result, it was found that tool rotation speed and tool plunge depth are highly effective on both microstructure and numerical modeling properties, apart from the tool geometry, which is one of the welding parameters.
Keywords: Al alloys; ANSYS approach; FEM; FSSW; microstructure